TINDAK PIDANA MAKAR TERHADAP KEUTUHAN WILAYAH NEGARA KESATUAN REPUBLIK INDONESIA BERDASARKAN PASAL 87 KUHP (ANALISIS YURIDIS TERHADAP GERAKAN RIAU MERDEKA TAHUN 1999) - Syefri Alpat Lukman; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Attack is derived from the word ‘aanslag’ (Netherlands), which according to the literal meaning an attack or an assault. But the Criminal Code specially interpreted that the plot to commit an act already exists, if the will of the perpetrator is already visible in the form of the beginning of implementation (wan begin uit voering) in the sense contemplated by Article 53 of the Criminal Code (Article 87 of the Criminal Code). The criminal act of treason is a crime that is associated with security issues of the country and the safety of the country. The criminal acts of treason regulated in Book II, Chapter I of the Criminal Code on crimes violate the security of the country. Criminal assaults links with criminal offenses experiment. Where in if a criminal offense experiment has three elements: the intention and the beginning of implementation, and the implementation is not completed and not merely because his own. Thus, in the crime of treason has two important elements, namely: the intention and the beginning of implementation.This research is a normative legal research or can be also called the doctrinal legal research. The result of research is, the Freedom Riau Movement who has violated the provisions of Article 106 of the Criminal Code so it’s categorized as a criminal offense of treason for having fulfilled the elements of treason in the form of the element of intention and execution starters elements along with the purposes prohibited in the Criminal Code,and the addition must maintain professionalisme working of police, confronting the police to enforce the law is its ties with the provisions of the Criminal Procedure Code. Because in the Criminal Procedure Code starting that law enforcement conducted by the police when their achieved a reports, complaints, and caught red-handed making it difficult for the police in Riau for research the Freedom Riau Movement. Plus explicitly unclear setting duties and powers of inquiry and investigation in Law No. 2 of 2002 on the Indonesian National Police so that the police are still referring to the Criminal Procedure Code to carry out their duties.Keywords: Criminal attacks-State Unitary- Criminal Code- Freedom Riau Movement